How altruistic organ donation may be (intrinsically) bad. Issue 10 (19th June 2018) - Saunders, Ben
Abstract : It has traditionally been assumed that organ donation must be altruistic, though the necessity of altruistic motivations has recently been questioned. Few, however, have questioned whether altruism is always a good motive. This paper considers the possibility that excessive altruism, or self-abnegation, may be intrinsically bad. How this may be so is illustrated with reference to Tom Hurka's account of the value of attitudes, which suggests that disproportionate love of one's own good—either excessive or deficient—is intrinsically bad. Whether or not we accept the details of this account, recognising that altruistic motivations may be intrinsically bad has important implications for organ procurement. One possible response is to say that we should take further measures to ensure that donors have good motives—that they are altruistic is no longer enough. An alternative is to say that, since altruistic donation need not be intrinsically good, we have less reason to object to other motivations.